A Reference Genome Assembly of Simmental Cattle, Bos taurus taurus. (13th January 2021) - Heaton, Michael P; Smith, Timothy P L; Bickhart, Derek M; Vander Ley, Brian L; Kuehn, Larry A; Oppenheimer, Jonas; Shafer, Wade R; Schuetze, Fred T; Stroud, Brad; McClure, Jennifer C; Barfield, Jennifer P; Blackburn, Harvey D; et al.
Abstract: Genomics research has relied principally on the establishment and curation of a reference genome for the species. However, it is increasingly recognized that a single reference genome cannot fully describe the extent of genetic variation within many widely distributed species. Pangenome representations are based on high-quality genome assemblies of multiple individuals and intended to represent the broadest possible diversity within a species. A Bovine Pangenome Consortium (BPC) has recently been established to begin assembling genomes from more than 600 recognized breeds of cattle, together with other related species to provide information on ancestral alleles and haplotypes. Previously reported de novo genome assemblies for Angus, Brahman, Hereford, and Highland breeds of cattle are part of the initial BPC effort. The present report describes a complete single haplotype assembly at chromosome-scale for a fullblood Simmental cow from an F1 bison–cattle hybrid fetus by trio binning. Simmental cattle, also known as Fleckvieh due to their red and white spots, originated in central Europe in the 1830s as a triple-purpose breed selected for draught, meat, and dairy production. There are over 50 million Simmental cattle in the world, known today for their fast growth and beef yields. This assembly (ARS_Simm1.0) is similar in length to the other bovine assemblies at 2.86 Gb, with a scaffold N50 of 102 Mb (max scaffold 156.8 Mb) and meets or exceeds the continuity of the best Bos taurus reference assemblies to date.